SIMPLE METHOD TO PRODUCE NANOPOROUS CARBON FOR VARIOUS APPLICATIONS BY PYROLYSIS OF SPECIALLY SYNTHESIZED PHENOLIC RESIN - Imam Prasetyo; Rochmadi Rochmadi; Teguh Ariyanto; Rakhmat Yunanto (Indonesian Journal of Chemistry, 2013)
Nanoporous carbon materials, a unique and useful material, have been widely used in many technologies such as separation processes, catalysis, energy storage, gas storage, energy conversion, etc. due to its high specific surface area and tunable porosity. In this research, nanoporous carbons were prepared using simple and innovative approach based on structural array of phenolic resin polymer without activation during carbonization process. The effect of phenolic reactant type and composition on pore structure and carbon surface morphologies was studied. Nanoporous carbon derived from resorcinol formaldehyde (RF) and from resorcinol phenol formaldehyde (RPF) polymers was suitable for electrode material supercapacitor and CO2 capture medium. RF-derived and RPF-derived carbons provide electrode material supercapacitor with specific capacitance up to 246 F/g, whereas carbonized RPF exhibited CO2 uptake of 10.63 mmol/g (at 3.5 MPa 298 K). Nanoporous carbon derived from resorcinol para-tert-butyl phenol formaldehyde (RTBPF) polymer exhibited attractive characteristics as methane storage media with methane uptake capacity as high as 8.98 mmol/g (at 3.5 MPa 298 K).